TAPAS: A tangible End-User Development tool supporting the repurposing of Pervasive Displays. (April 2017) - Turchi, Tommaso; Malizia, Alessio; Dix, Alan
Abstract: These days we are witnessing a spread of many new digital systems in public spaces featuring easy to use and engaging interaction modalities, such as multi-touch, gestures, tangible, and voice. This new user-centered paradigm — known as the NUI — aims to provide a more natural and rich experience to end users; this supports its adoption in many ubiquitous domains, as it naturally holds for Pervasive Displays: these systems are composed of variously-sized displays and support many-to-many interactions with the same public screens at the same time. Due to their public and moderated nature, users need an easy way of adapting them to heterogeneous usage contexts in order to support their long-term adoption. In this paper, we propose an End-User Development approach to this problem introducing TAPAS, a system that combines a tangible interaction with a puzzle metaphor, allowing users to create workflows on a Pervasive Display to satisfy their needs; its design and visual syntax stem from a study we carried out with designers, whose findings are also part of this work. We then carried out a preliminary evaluation of our system with second year university students and interaction designers, gathering useful feedback to improve TAPAS and employ it in many other domains. Abstract : Highlights: A novel application for Pervasive Displays combining a TUI with a projected visual interface is presented. The design rationale and study behind the application design is presented. Two preliminary evaluations of TAPAS are presented and discussed. The main challenges faced by Tangible Programming on Pervasive Displays are highlighted.